Karakteristik Organoleptik dan Kimia Snack Nori dari Daun Chaya dan Tapioka - Miftahul Huda; Sri Rejeki Retna Pertiwi; Muhammad Fakih Kurniawan (Universitas Muhammadiyah Semarang, 2022)
The market opportunity for snack products is currently very high, this is indicated by the many different shapes and flavors. Snack nori is one form of the diversity of snack products and is an alternative to healthy snacks. Chaya (C. aconitifolius) is an opportunity for Chaya (C. aconitifolius) as a substitute for alternative raw materials, which are abundant and have a high crude fiber content. This study aims to utilize chaya (C. aconitifolius) in the manufacture of nori snacks with the addition of tapioca. The experimental design used was a completely randomized design (CRD) with two factors, namely factor A was the formulation of the ratio of chaya and tapioca (60:40, 40:60, 80:20) and factor B was the processing method (oven and frying. The results of data analysis used analysis of variance (ANOVA) with Duncan's Advanced Test with a 95% confidence interval. The selected nori snack is a comparison of chaya and tapioca (80:20) with the frying processing method with a color sensory value of 7.32 (towards greenish black), taste of (towards savory), aroma of 7.26 (towards very unpleasant). rancid), and texture of 7.65 (towards crunchy); color hedonic score 6.33, taste 6.46, 6.47, texture 6.54, overall 6.54 each towards very like. The results of the chemical test of the selected nori snack were 3.11% water content, 3.05% ash content, 19.7% protein content, 9.72% fat content, 67.53% carbohydrate content and 14.3% crude fiber.